Acute limb ischemia following perineal reconstruction in lithotomy position: take-home message for plastic surgeons - Gianluca Sapino; Sebastien Deglise; Wassim Raffoul; Pietro G. di Summa (Archives of Plastic Surgery, 2021)
Despite the extensive use of lithotomy position in several plastic surgery procedures, most reports regarding the related incidence of complications are presented in the urologic, gynecologic, and anesthesiologic fields. We present the case of a 54-year-old male patient. polytrauma patient who underwent internal iliac artery embolization leading to extensive gluteal necrosis requiring: debridement, abdominoperineal resection and composite anterolateral thigh flap reconstruction with prolonged lithotomy position. The patient presented lower limb ischemia briefly after surgical theater. A computed tomography scan revealed the obstruction of the left superficial femoral artery requiring emergency revascularization. Arterial thrombosis is a potentially devastating complication and plastic surgeons should be aware of the possible dangers when performing surgeries in prolonged lithotomy position. Preoperative detection of patients at high risks for developing complications should be performed in order to implement preventive measures and avoid potentially life-threatening sequelae.